Correlation between Emotional Intelligence and Leadership Style among Nurse Managers - Ibrahim Saleem Mahdi, Raad Kareem Faraj (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The study aims at assessing the level of emotional intelligence as well as leadership styles and detecting the relationship between emotional intelligence and leadership styles. Materials and methods: A descriptive study, correlational design that is initiated for the period of October 1st 2021 to June 1st, 2022. The sample of the study includes 260 nurse managers was selected by convenient sampling method (non-probability sample). The setting of the study includes the teaching hospitals in Baghdad city. Two scales were used in the current study; Emotional Intelligence Scales which comprised of 45 items and Leadership Styles which comprised of 26 items distributed on four dimensions: 5 items for Leading Change; 7 items for leading nurses; 6 items for Results Driven; 5 items for Communications. The data have been collected through the utilization of the self-administrative report as a mean of data collection. Statistical analyses were conducted by using statistical package for social science (IBM SPSS Statistics) version 26.0. Results: The study found that 95% of nurse managers are associated with high level of emotional intelligence (M±SD= 189.42±13.084), nurse managers show good competencies regarding leadership of change style (M±SD= 21.23±2.664), subordinate leadership style (M±SD= 29.61±3.863), focus on result style (M±SD= 25.31±3.075) and leadership of communication style (M±SD= 21.60±2.491). Emotional intelligence of nurse managers is positively correlated with leadership style of change, subordinate leadership, and leadership of communication style at p-value= .001, .001, and .033. Conclusions: Based on the study finding, the study concludes that nurse managers are associated with high emotional intelligence and good leadership competencies. There is evidence of a two-way relationship between emotional intelligence and leadership style competencies among nurse managers. Recommendations: The study is recommended The Health Institution administrators need to design a training program to improve conflict management and emotional intelligence for nurses to effectively manage conflicts among them which is inevitable in health care institutions.